Composting for a fertile solo: process and poetics in the performance galhada (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This text describes aspects of the solo play galhada (branching out), in times of fissure. The process involved artistic collaboration in the areas of dramaturgy, visuals, acting, movement, and sound. Composting is a metaphor for this collective creation that transcended pre-established functions, with inventive and critical materials and alterities intermingled in scenic humus. This term is connected to the theme of the show, which discusses the devastation of the Anthropocene. The scene operates with principles of performer-led-dramaturgy and elements of the lecture play in a performative poetics that combines bodily research, live music, pre-recorded sounds, and video images.
Keywords: anthropocene; composting; performer-led-dramaturgy